Koppelung agrarökonomischer und hydrologischer Modelle; Coupling of Agricultural Economic and Hydrological Models - Horst Gom̈ann; Peter Kreins; Ralf Kunkel; Frank Wendland (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– The objective of the paper is to show the potential of interdisciplinary model networks consisting of agricultural economic and natural science models performing integrated impact assessments of agri-environmental policies. The potentials are exemplified using a coupling of the agricultural sector model RAUMIS with the hydrological models GROWA98 and WEKU in the scope of diffuse agricultural nitrogen immission into waterbodies. A brief classification of applied indicators is given. A key element for policy impact analyses are the relationships between the environmental indicator categories Driving Force, State and Response. The major relationships within this environmental scope as well as the modeling are explained. The presented model network represents a first area wide, regionally differentiated, consistent link-up between the Driving Force indicator "nitrogen balance surplus", the State indicator "nitrogen(nitrate)concentration" and the response indicators. The results show that due to the local characteristics quite different shares of the agricultural nitrogen surplus finally enters the ground and surface waters. Hence, assessing the trade-offs of agri-environmental water protection measures requires an inclusion of natural local characteristics. The integrated consideration of the complex relationships and a comprehensive implementation of local characteristics allows to develop more efficient water pollution control measures.
Keywords: 330; Geologie; Agrarökonomik; Politikberatung; Interdisziplinäre Forschung